HIGH HEART RATE AS A POTENTIAL RISK FACTOR FOR DEVELOPMENT OF CARDIOVASCULAR DISEASES IN WOMEN WITH RHEUMATOID ARTHRITIS - D. S. Novikova; T. V. Popkova; A. N. Gerasimov; A. V. Volkov; E. L. Nasonov (Столичная издательская компания, 2015)
Aim. To study relationship between heart rate (HR) and traditional risk factors for cardiovascular diseases (TRF for CVD), subclinical structural and functional changes in the heart and vessels, as well as the activity and severity of rheumatoid inflammation in women with rheumatoid arthritis (RA). Material and methods. A total of 291 female patients less than 60 years of age with a definite diagnosis of RA were examined. The control group consisted of 125 women without rheumatic diseases. Aside from clinical symptoms, activity and severity level of RA, the presence of main TRF for CVD were assessed, 24 h Holter ECG monitoring (24-h ECG), duplex scanning of common carotid arteries, transthoracic echocardiography were performed and the serum levels of inflammatory markers were determined.  Results. RA patients compared with the control group women had higher values of minimum (52.3±0.4 vs 47.5±0.4; p<0.001) and mean (78.5±0.5 vs 75.5±0.5; p<0.001) HR according to 24-h ECG, after adjustment for main TRF for CVD (age, arterial hypertension, menopause, levels of total cholesterol, triglycerides, high density lipoprotein cholesterol). Accelerated HR in RA directly correlated with an increased joint functional disability index - HAQ, RA severity index, the level of inflammatory markers and administration of leflunomide after adjustment for age (р<0.05). Patients with HR≥86 beats per minute compared with RA patients with values of HR≤71 beats per min had lower total cholesterol (5.84±0.13 vs 5.11±0.17; p=0.001) and low density lipoprotein cholesterol levels (4.06±0.13 vs 3.28±0.18; p=0.001), longer duration, higher activity (Visual Analog Pain Scale, DAS28, extra-articular manifestations of RA, concentration of proinflammatory markers) and severity level of RA (severity index, HAQ, radiological stage III/IV), as well as  higher percentage of left ventricular diastolic dysfunction (LVDD) after adjustment for age. Conclusion. According to 24-h ECG, an increase in mean HR values in women with RA is associated with activity , severity of rheumatoid inflammation and LVDD. Prospective studies are needed to determine the role of accelerated HR as a risk factor for development of CVD and the feasibility of preventive measures creation aimed to lower HR to prevent cardiovascular events in RA.